Koreksi Etika Bisnis Islam terhadap Sistem Ekonomi Kapitalis dan Sosialis - Pratiwi, Nurul; Rahmawati Muin; Nur Azizah (Al-Buhuts, 2024)
This research aims to analyze the correction of Islamic business ethics to the capitalist and socialist economic systems. This research uses a qualitative method with a library research approach. Islamic business ethics correct the capitalist economic system by emphasizing the principles of justice, balance, and social responsibility. Capitalist and socialist economic systems have shortcomings in terms of business ethics. Capitalism tends to prioritize profit and ignore social justice, while socialism negates private ownership and individual rights. Islamic business ethics come as a solution to balance the two systems. Islamic business ethics also correct the socialist economic system by recognizing private property rights and individual freedom. By applying Islamic business ethics, businesses can be more oriented towards social and environmental interests, as well as more fair in the distribution of wealth.